PENGGUNAAN MEDIA POWERPOINT DALAM PEMBELAJARAN MULTIMEDIA BERDASARKAN PRINSIP EFEKTIF DAN EFISIEN DI SEKOLAH DASAR - Widyawati, S.Pd; Prastowo, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the use of PowerPoint as a multimedia learning tool based on the principles of effectiveness and efficiency in elementary schools. A qualitative approach was used, with data collected through interviews with a teacher. The data analysis technique followed the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The research was conducted at an elementary school in Yogyakarta, involving one teacher as the informant. The results show that the effective and efficient use of multimedia-based PowerPoint is characterized by student centered presentations, the creation of educational interactions between teachers and students through slides, the integration of various media and teaching methods, and the availability of adequate learning facilities. PowerPoint can serve as a solution for elementary schools that are still facing challenges related to students’ lack of understanding and engagement in learning.